ANALISIS PENGARUH KUALITAS PRODUK,KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN PADA MINYAK GORENG KEMASAN CV.INDO SARI ABADI - Piter Liman; Muhammad Alfani; Sulastini Sulastini (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2016)
This study aimed to, test the significant influence partially on the Product Quality Customer Satisfaction, Quality of Service testing the significant influence partially on Customer Satisfaction and, to test significant influence price perceptions partially to Customer Satisfaction.Methods of analysis using multiple linear regression equation .Populasi in this study were all customers or consumers cooking oil CV.Indo Sari Abadi .Sampel study of 50 people .Pengujian partially Effect of Variable Product Quality (X1) to Customer Satisfaction, is equal to 0,511, with thus, the hypothesis that product quality is not positive or significant effect on customer satisfaction in Edible Oils Packaging CV.Indo Sari Abadi Banjarmasin proven rejected. Effect of Variable Quality of Service (X2) to the value t variable quality of service is equal to -0,114, Thus, the hypothesis that service quality is not positive or significant effect on customer satisfaction in Edible Oils Packaging CV.Indo Sari Abadi Banjarmasin proven rejected. Variables Influence Perception Price (X3) on Customer Satisfaction in Edible Oils Packaging CV.Indo Sari Abadi Banjarmasin.Nilai t Variable Perception is the price of 15,569, this result is greater than the t-table is thus partially 2,011.Dengan price perception have a significant impact on customer satisfaction on bottled cooking oil CV.Indo Sari Abadi Banjarmasin probability variable error rate of 0,00 (less than 0,05) .With thus, the hypothesis that the perception of price positive effect on customer satisfaction on oil bottled cooking CV.Indo Sari Abadi Banjarmasin proved acceptable.